Effectiveness of Tax Incentives in Increasing Investment in Green Technology and Green Energy - Sapar, Jhony Fahrin; Kusuma, Eka Raya Hadi (Advances in Taxation Research, 2025)
Purpose: This study evaluates the effectiveness of tax incentives in promoting investments in green technology and renewable energy. It aims to explore how fiscal policies influence corporate investment behaviors, identify factors contributing to their success or limitations, and assess their role in supporting global sustainability objectives. Research Design and Methodology: The research adopts a systematic literature review (SLR) approach to synthesize evidence from diverse contexts and methodologies. By analyzing academic studies and reports published after 2015, the study identifies patterns, challenges, and opportunities related to the design, implementation, and outcomes of tax incentives in green investments. The analysis integrates both quantitative and qualitative dimensions to provide a comprehensive perspective. Findings and Discussion: The findings reveal that tax incentives significantly reduce financial barriers, fostering investments in renewable energy and green technologies. However, their effectiveness depends on well-structured designs tailored to industry needs, efficient administrative processes, and integration with other sustainability policies. The discussion highlights the short-term and long-term impacts of tax incentives, including increased green innovation, capacity expansion in renewable energy, and contributions to Sustainable Development Goals (SDGs). Challenges such as administrative complexity and limited awareness among businesses, especially SMEs, have also been identified. Implications: This study offers practical and managerial insights for policymakers and stakeholders, emphasizing the need for simplified procedures, enhanced awareness, and coordinated policies. By addressing gaps in current practices, the study contributes to the design of more effective fiscal measures for accelerating sustainable investments and achieving global environmental goals.